2006
DOI: 10.1128/aac.00303-06
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Levels and rpoB Gene Mutations among In Vitro-Selected Rifampin-Resistant Mycobacterium tuberculosis Mutants

Abstract: The distribution and resistance levels of 189 in vitro-selected rifampin-resistant Mycobacterium tuberculosis mutants of Beijing and other genotypes were determined. Apart from a higher amount of codon 522 point mutations and large deletions, a spread of mutations similar to that reported for clinical isolates was seen. Most mutations were correlated with high-level resistance; a lower level, or a MIC of <16 mg/liter, was associated with codon 522 mutations. Multiple mutations were detected in two Beijing muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 25 publications
4
44
1
Order By: Relevance
“…These isolates clustered with the atypical Beijing strains from the WC which had a nsSNP at codon 516 (GAC3GTC) and the Ϫ17 inhA promoter mutation, suggesting interprovincial spread. This finding was contrary to previous reports, which suggested that atypical Beijing strains are attenuated in their ability to transmit (9,14), while the mutation at codon 516 (GAC3GTC) would have been expected to further compromise the ability of these strains to transmit unless compensatory mutations were present or the 4 529 CGA3CCA 1 CGA3CAA 1 CGA3GGA 1 531 TCG3TGG 17 8 2 3 3 2 2 TCG3TTG 132 169 110 54 5 58 42 5 11 TCG3CAG 3 3 TCG3TTC 1 1 (4,7,10). c Under-represented in the in vitro generated rifampin-resistant mutants (z-test ͓P Ͻ 0.001͔).…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…These isolates clustered with the atypical Beijing strains from the WC which had a nsSNP at codon 516 (GAC3GTC) and the Ϫ17 inhA promoter mutation, suggesting interprovincial spread. This finding was contrary to previous reports, which suggested that atypical Beijing strains are attenuated in their ability to transmit (9,14), while the mutation at codon 516 (GAC3GTC) would have been expected to further compromise the ability of these strains to transmit unless compensatory mutations were present or the 4 529 CGA3CCA 1 CGA3CAA 1 CGA3GGA 1 531 TCG3TGG 17 8 2 3 3 2 2 TCG3TTG 132 169 110 54 5 58 42 5 11 TCG3CAG 3 3 TCG3TTC 1 1 (4,7,10). c Under-represented in the in vitro generated rifampin-resistant mutants (z-test ͓P Ͻ 0.001͔).…”
contrasting
confidence: 56%
“…d Over-represented in the in vitro-generated rifampin-resistant mutants (z-test ͓P Ͻ 0.001͔). e Eleven different deletion events (7,10 epidemiological context allowed transmission to occur. Analysis of the host population in the EC region showed human immunodeficiency virus (HIV) coinfection to be a risk factor for the spread of the atypical Beijing strains (z-test for the hypothesis that a proportion of HIV-positive cases ϭ 0.42, P ϭ 0.029).…”
mentioning
confidence: 99%
“…A similar mutation at this codon (S→L) was recently reported to correlate with a low level of resistance in clinical isolates and to be associated with a bacterial fitness deficit (Mariam et al 2004, Huitric et al 2006. Thus, this isolate could help in understanding the real value of this codon change in the biology of Mycobacterium and the sensitivity of the BACTEC system for the diagnosis of DR-TB.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, some mutations in rpo B gene, such as rpo B S531L, H526Y, H526D and H526R, are often associated with high levels of rifampicin resistance, while mutations including rpo B L511P, H526L, H526N, L533P and I572F are generally linked to low levels of rifampicin resistance (Huitric et al., 2006; Van Deun et al., 2009). Similar to that, kat G mutations are often associated with high levels of isoniazid resistance, whereas inh A mutations with low levels (Fenner et al., 2012; van Soolingen et al., 2000; Vilcheze & Jacobs, 2014).…”
Section: Characteristics and Diversity Of Drug Resistance‐associated mentioning
confidence: 99%
“…For instance, the predominant mutations associated with high level of drug resistance and a low or no biological cost, such as kat G S315T, rpo B S531L, rps L K43R and gyr A D94G (conferring resistance to isoniazid, rifampicin, streptomycin and fluoroquinolones respectively), are more frequently found in clinical drug‐resistant isolates (Billington et al., 1999; Bottger et al., 1998; Campbell et al., 2011; Casali et al., 2014; Gagneux, Burgos, et al., 2006; Gagneux, Long, et al., 2006; Mariam et al., 2004; Pym et al., 2002). Indeed, some of these resistance mutations do not reduce bacterial fitness in the absence of treatment (Bergval, Schuitema, Klatser, & Anthony, 2009; Huitric et al., 2006; Mariam et al., 2004). It is worth noting that MDR and XDR strains associated with outbreaks often carried these mutations explaining the successful spread of these highly drug‐resistant strains in the community (Casali et al., 2014; Cohen et al., 2015; Niehaus, Mlisana, Gandhi, Mathema, & Brust, 2015; de Vos et al., 2013).…”
Section: Fitness Cost Of Drug Resistance‐associated Mutationsmentioning
confidence: 99%